Assessment Protocol to Evaluate the Degree of Conservation of Habitats of Community Interest: A Case Study for the 5220* HCI in the Westernmost Localities of Europe. - Hidalgo-Triana, Noelia; Casimiro-Soriguer Solanas, Federico; Solakis Tena, Andros; Manteca Bautista, David; Picornell Rodríguez, Antonio; García Sánchez, José; Navarro-del-Águila, María Teresa; Pérez-Latorre, Andrés Vicente (MDPI, 2023)
The westernmost European nucleus of the 5220* Habitat of Community Interest (HCI) is located in the province of Málaga (Andalusia). In this area, the 5220* HCI is characterized by the presence of scrublands of Gymnosporia senegalensis subsp. europaea. This is a relict species in Europe, with inhabits only in the southeast of the Iberian Peninsula. The westernmost Iberian nuclei of the 5220* HCI are constituted by three isolated nuclei (Málaga–Rincón de la Victoria; Torremolinos; and Pizarra). These nuclei have been only partially mapped. The objectives were: to map the 5220* HCI characterized by G. senegalensis subsp. europaea in detail; to evaluate its degree of conservation (DC); and to identify the chronosequences of the evolution of this habitat from 1957 to 2021, and its fragmentation. Our results have contributed to generating a 1:10,000 scale cartography of the habitat. In general, the DC obtained was from good to excellent. With an excellent DC value, one inland locality (Pizarra) was highlighted. However, the highest reduction in the value of DC was observed in the localities of Torremolinos and Málaga–Rincón de la Victoria which, in addition, have reduced the area of occupancy (AOO) and are fragmented. It is important to note that some areas of Málaga–Rincón de la Victoria reached excellent values of DC, indicating the need to carry out protection.
Keywords: Flora - Mediterráneo (Región); Habitat Directive 92/43/EEZ; Fragmentation; Relictual; Priority habitat; Mediterranean flora; Maytenus senegalensis subsp. europaeus